Low-energy earth–air heat exchanger cooling system for buildings in hot and humid malaysia - Sanusi, Aliyah Nur Zafirah; Shao, Li; Keumala, Nila Inangda (Springer, 2015)
This chapter presents an extended exploration of the performance of low-energy earth–air heat exchanger (EAHE) cooling in hot and humid Malaysia from the published work of Sanusi (2013). The increasing demand of air-conditioning for cooling purposes motivates this investigation in search for better cooling alternatives. The passive technology, where soil underground was used as a heat sink to produce cooler air, has yet to be investigated further in hot and humid countries. This work, the passive technology, is tested by carrying out two interconnected field investigations: soil temperature measurement and the earth pipe cooling experiment for 1 year. In 1 year, soil temperature distribution at 1 m depth fluctuates, influenced by the different seasons in a year. However, the soil at 1 m depth is cooler than deeper soil during the wet season. Therefore, for investigating the EAHE cooling performance for 1 year, the pipe was buried at 1 m depth at the same test site. A significant temperature drop was found in the 1-m-depth-buried pipe: up to 6.3 and 8.6 °C, respective to the seasons of the year. Thermal comfort of air temperature at the buried pipe outlet was analyzed with Khedari thermal comfort chart, and the result has shown that the buried pipe outlet air temperatures are within the range of thermal comfort conditions for hot/humid countries. This study has showed a potential of earth pipe cooling technology buildings in Malaysia.